UnMarketing : everything has changed and nothing is different - Stratten, Scott, (Wiley, 2017)
"Stop marketing. Start UnMarketing. No one likes cold calls at dinnertime, junk mail overflowing your mailbox, and advertisements that interrupt your favorite shows. If this is "marketing," then the world would probably prefer whatever is the opposite of that. If you're ready to stop marketing and start engaging, then welcome to UnMarketing. The landscape of business-customer relationships is changing, and UnMarketing gives you innovative ways out of the old "Push and Pray" rut. Instead, draw the right customers to you through listening and engagement, enabling you to build trust and position yourself as their logical choice when they need you. This second edition includes new information on the rapidly changing marketing landscape, including details on targeted ads and search, Snapchat, brand engagement, and more"--